SOCS3, a Major Regulator of Infection and Inflammation - Rottenberg, Martin E.; Carow, Berit (Frontiers in Immunology, 2014)
In this review we describe the critical roles of Suppressor of cytokine signalling-3 (SOCS3) in modulating the outcome of infections and autoimmune diseases as well as the underlying mechanisms. SOCS3 regulates excess of cytokine or hormone signalling usually preventing, but in some cases aggravating, a variety of diseases. A main role of SOCS3 results from its binding to both the JAK kinase and the cytokine receptor, which results in the inhibition of STAT3 activation. Available data also indicates that SOCS3 can regulate signalling via other STATs than STAT3 and also control cellular pathways unrelated to STAT activation. SOCS3 might either hamper JAK activation directly or by mediating the ubiquitination and subsequent proteasome degradation of the cytokine/ growth factor/ hormone receptor. Inflammation and infection stimulates SOCS3 expression in different myeloid and lymphoid cell populations as well as in different non-hematopoietic cells. The accumulated data suggest a relevant program coordinated by SOCS3 in different cell populations, devoted to the control of immune homeostasis in physiological and pathological conditions such as infection and autoimmunity.